Deciphering inter-catchment groundwater flow: A water balance perspective in the Choshui River Basin, Taiwan - Hsin-Yu Chen; Hsin-Fu Yeh; Chien-Chung Ke; Ya-Sin Yang; Chia-Chi Huang (Journal of Hydrology: Regional Studies, 2024)
Study region: Five catchments in upstream Choshui River Basin, Taiwan. Study focus: Inter-catchment groundwater flow (IGF)is commonly assumed negligible role in a catchment water balance due to its obscure nature. Many studies required detailed on-site geological information to analyze and confirm the significance of IGF. In contrast to these studies, this study investigated IGF using the rainfall-runoff model combined with the deterministic optimization algorithm and the stochastic generalized likelihood uncertainty estimation method, relying on simple and easily accessible water balance data. New hydrological insights for the region: The results showed that the hydrological environment was non-stationary, and IGF inclusion in the model improved its simulation performance. Though IGF direction varied among the catchments, at least three were found with significant IGF potential, with one of the catchments accounting for 30 % (505 mm) of the yearly precipitation. Ignoring IGF may lead to larger errors, especially in smaller catchments and during the dry season. Overall, this study highlights the importance of considering IGF in a catchment water balance and provides insights into the hydrological cycle.